Improving Students’ Reading Comprehension through Cooperative Language Learning and Reading Strategies - Wirhayati Wirhayati (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Reading is the active process of understanding print and texts. The effective of teaching reading is applied to improve students’ reading skills. In addition, reading cannot be separated by comprehension. Since reading is complex developmental challenges that we know to be intertwined with many other developmental accomplishments: attention, memory, language, and motivation, lecturers select and use a reading strategy (such as rereading or asking questions) that will help them reconnect with the meaning of the text. And students are learning subject-specific content through authentic reading tasks. This study aims to identify the activities of teaching reading using cooperative language learning (CLL) and reading strategies at students of Pamulang University (UNPAM). It is focused on the effective of teaching reading through cooperative language learning and reading strategies. For The Data source is the English students who are learning in the second reading class. Qualitative approach is used to analyze the study and the results are described and analyzed in essay form. Based on the data analysis, the implementation of cooperative language learning method and reading strategies in teaching reading has an important significant that students are active and interested in their reading class. The materials used are from many sources, and some topics given to discuss are various in a group. It is applied in the class activities to know the achievement of students’ reading comprehension.